Hematopoietic kit deficiency, rather than lack of mast cells, protects mice from obesity and insulin resistance - Gutierrez, Dario Alejandro; Herzig, Stephan; Rodewald, Hans-Reimer (Cell metabolism, 2015)
Summary: Obesity, insulin resistance, and related pathologies are associated with immune-mediated chronic inflammation. Kit mutant mice are protected from diet-induced obesity and associated co-morbidities, and this phenotype has previously been attributed to their lack of mast cells. We performed a comprehensive metabolic analysis of Kit-dependent KitW/Wv and Kit-independent Cpa3Cre/+ mast-cell-deficient mouse strains, employing diet-induced or genetic (LepOb/Ob background) models of obesity. Our results show that mast cell deficiency, in the absence of Kit mutations, plays no role in the regulation of weight gain or insulin resistance. Moreover, we provide evidence that the metabolic phenotype observed in Kit mutant mice, while independent of mast cells, is immune regulated. Our data underscore the value of definitive mast cell deficiency models to conclusively test the involvement of this enigmatic cell in immune-mediated pathologies and identify Kit as a key hematopoietic factor in the pathogenesis of metabolic syndrome.
Gesehen am 03.08.2017